Applying personal scrum methodology in system development for project-based learning course / Nor Asma Mohd Zin ... [et al.] - Mohd Zin, Nor Asma; Mazlan, Ain Nadia; Arifin, Noorfadzilah; Abdul Rahman, Noorihan; Ahmad, Marina; Manaf, Maznie Manaf (Unit Penerbitan UiTM Kelantan, 2024)
Educators today are tasked with developing lifelong learners who can survive and thrive in a global knowledge economy. Hence, project-based learning is seen as one of the ways an educator can use to promote learner autonomy in higher education. The software development course at Universiti Teknologi MARA(UiTM)is one of the project-based learning courses that require students to go through all phases of system development to solve real case studies. However, some students found that project-based learning is quite challenging since it often involves long-term projects that require clear time management skills. This long-term project needs sustained motivation from students. Without proper guidance and milestones, students may lose interest or fail to stay engaged. Agile methodology is suitable to be implemented for system development in realising project-based learning. Scrum methodology, a framework derived from Agile, helps ensure that system development is completed on time by dividing the development process into small, manageable cycles called sprints. The time-boxed nature of sprints helps avoid scope creep and delays, as the team must complete specific deliverables within a set time frame. In this paper, the development of a web-based system for home cleaning service is demonstrated using the Personal ScrumMethodology.